Implementasi Analisis Kebutuhan Pelatihan Dalam Pengembangan Karyawan Di Unit Collection & Recovery, Permata Bank - Rafly, Muhammad; Yatimah, Durotul; Sutisna, Anan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research analyzed the implementation of training need analysis (TNA) for employee development at Permata Bank's Collection & Recovery Unit in East Jakarta. The issue stemmed from a mismatch between training programs and employee needs, leading to suboptimal unit performance. The study aimed to describe training needs, TNA application, and influencing factors. Employing a descriptive qualitative case study method, data was gathered via interviews, observations, and documentation, validated through triangulation. Findings revealed TNA implementation was suboptimal due to L&D implementers' limited competence and insufficient employee involvement, resulting in irrelevant and ineffective training. Inhibiting factors included minimal management support, time constraints, and resistance to change, despite adequate training facilities. Recommendations included specialized TNA training for L&D, standardized TNA guidelines, benchmarking, and regular evaluation for continuous improvement.